KAJIAN POTENSI ARUS SUNGAI LAGAN DI DESA LAGAN TENGAH KAB. TANJAB TIMUR SEBAGAI PEMBANGKIT LISTRIK - Myson Myson (Jurnal Ilmiah Universitas Batanghari Jambi, 2013)
Lagan village Tengan Eastern District Geragai Tanjab District is one of the village is still experiencing problems in meeting the electricity needs for the community, but the middle of the village crossed by the river lagan lagan.River is a river lagan adequate when used as a power plant to meet the needs of rural communities. Based on the observations and calculations is known that power can be generated by current and discharge sengai amounted to 4821 watts.Key word:  The river lagan, Tanjab East Electricity, Power Flow